Gender Struggles : Wage-Earning Women and Male-Dominated Unions in Postwar Japan - Gerteis, Christopher, 1968- (Book collections on Project MUSE., 2009)
By showing how unions raised the wages of male workers in part by transforming working-class women into middle-class housewives, the author demonstrates that organized labour's discourse on womanhood prevented unions from linking with the emerging woman-led, neighbourhood centred organizations that typified social movements.